Ke stanovení hodnoty práva stavby – část III - Bradáč, Albert (Akademické nakladatelství CERM, 2017)
Příspěvek navazuje na předchozí příspěvky autora, jež byly uveřejněny v předchozích číslech časopisu Soudní inženýrství. Příspěvky se zabývaly mírou kapitalizace, stanovením hodnoty pozemku, zatíženého právem stavby, oceněním práva stavby bez zřízené stavby a vlivem ceny stavby. Tento příspěvek obsahuje shrnutí předchozích úvah.

The contribution builds on previous contributions of the author, which were published in previous numbers of the journal Forensic engineering. The contributions address the degree of capitalization, by setting the value of the land, burdened the right of construction, valuation of building rights without the established structures and the influence of the price of construction. This post contains a summary of the previous considerations.
To Determine the Value of Building Rights – Part III
Keywords: Občanský zákoník; právo stavby; nájemné; výnosové ocenění; vzorce pro výnosové ocenění; míra kapitalizace; odúročení (diskontování); úročitel; znalec; odhadce; ocenění majetku; pozemek; stavba; Civil Code; the right to build; rent; the yield valuation; formulas for yield valuation; capitalization rate; discounting; interest factor; expert; appraiser; property valuation; land; construction